Acetylation Profiles in the Metabolic Process of Glioma-Associated Seizures - Xu, Ya-Wen; Lin, Peng; Zheng, Shu-Fa; Huang, Wen; Lin, Zhang-Ya; Shang-Guan, Huang-Cheng; Lin, Yuan-Xiang; Yao, Pei-Sen; Kang, De-Zhi (Frontiers in Neurology, 2021)
Objective: We test the hypothesis that lysine acetylation is involved in the metabolic process of glioma-associated seizures (GAS). Methods: We used label-free mass spectrometry-based quantitative proteomics to quantify dynamic changes of protein acetylation between gliomas with seizure (CA1 group) and gliomas without seizure (CA2 group). Furthermore, differences of acetyltransferase and deacetylase expression between CA1 and CA2 groups were performed by a quantitative proteomic study. We further classified acetylated proteins into groups according to cell component, molecular function, and biological process. In addition, metabolic pathways and protein interaction networks were analyzed. Regulated acetyltransferases and acetylated profiles were validated by PRM and Western blot. Results: We detected 169 downregulated lysine acetylation sites of 134 proteins and 39 upregulated lysine acetylation sites of 35 proteins in glioma with seizures based on acetylome. We detected 407 regulated proteins by proteomics, from which ACAT2 and ACAA2 were the differentially regulated enzymes in the acetylation of GAS. According to the KEGG analysis, the upregulated acetylated proteins within the PPIs were mapped to pathways involved in the TCA cycle, oxidative phosphorylation, biosynthesis of amino acids, and carbon metabolism. The downregulated acetylated proteins within the PPIs were mapped to pathways involved in fatty acid metabolism, oxidative phosphorylation, TCA cycle, and necroptosis. Regulated ACAT2 expression and acetylated profiles were validated by PRM and Western blot. Conclusions: The data support the hypothesis that regulated protein acetylation is involved in the metabolic process of GAS, which may be induced by acetyl-CoA acetyltransferases.